2017
DOI: 10.1016/j.jstrokecerebrovasdis.2017.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pre-Stroke Depressive Symptoms, Fatalism, and Social Support on Disability after Stroke

Abstract: Background Psychological and social factors have been linked to stroke mortality; however, their impact on stroke disability is unclear. The purpose of this study was to evaluate the impact of pre-stroke fatalism, depressive symptoms, and social support on 90-day neurological, functional, and cognitive outcomes. Methods Ischemic strokes (2008–2011) were identified from the Brain Attack Surveillance in Corpus Christi Project. Validated scales were used to assess fatalism, depressive symptoms, and social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Stroke is one of the most server conditions, which often results in high disability, mortality, and morbidity. [ 1 – 3 ] It is reported that it has affected 7 million adults in America with 3.0% of the population from 2007 to 2010, according to the American Stroke Association statistics. [ 4 , 5 ] Of those populations, many stroke survivors often suffer from limb paralysis, abnormal gait, aphasia, and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the most server conditions, which often results in high disability, mortality, and morbidity. [ 1 – 3 ] It is reported that it has affected 7 million adults in America with 3.0% of the population from 2007 to 2010, according to the American Stroke Association statistics. [ 4 , 5 ] Of those populations, many stroke survivors often suffer from limb paralysis, abnormal gait, aphasia, and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…• Comorbidities: Medical comorbidities and their severity are critical determinants of patient outcome and should be taken into account in prognostic tools [124][125][126]. Premorbid cognition, mental health, and personality are under-ascertained yet may similarly contribute to patient-centered outcomes [127,128].…”
Section: Panel Discussion Of the Approachmentioning
confidence: 99%
“…Limited data exist on the relation between anxiety disorders and stroke incidence 33. However, there is a scarcity of studies investigating the relationship between prestroke psychiatric morbidity and the severity of stroke or outcome after stroke: two groups demonstrated associations between prestroke depression and stroke severity as well as functional outcome 11,12. Data on the impact of prestroke dementia on stroke severity and outcome are also consistent in that pre-existing dementia is associated with a higher burden of disability and higher rates of institutionalization after stroke 3436.…”
Section: Discussionmentioning
confidence: 99%
“…Poststroke depression, for example, affects nearly a third of all stroke survivors within five years following stroke,9 and poststroke depression severity predicts the extent of impairment in activities of daily living after stroke 10. Pre-existing affective disorder, on the other hand, has been demonstrated to predict more severe strokes on admittance and to negatively impact functional and cognitive outcomes after stroke 11,12. Recent data from a large Swedish register study indicate that patients with prestroke psychosis showed a poorer outcome and poorer utilization of secondary pharmacological prevention after stroke 13.…”
Section: Introductionmentioning
confidence: 99%